ANALISIS BIBLIOMETRIC DARI PROGRAM HIBAH (BIBLIOMETRIC OF GRANTS PROGRAM) - Iqbal M. Iqbal Firmansyah; Rita Myrna; Ida Widianingsih (Shaut Al-Maktabah : Jurnal Perpustakaan, Arsip dan Dokumentasi, 2021)
This article is a bibliometric analysis of articles published in Scopus indexed journals that discuss grant programs using Vosviewer. The purpose of bibliometric analysis is aimed at knowing the development of studies related to the grant program. Specifically, this study looks at the development of citations, publication trends, author collaboration, trend terms titles, trend terms author keywords, trend terms abstracts, and state statistics on grant program articles in 2015-2020. Data were collected from the Scopus database using the keyword "grants program". Furthermore, the author uses vosviewer software to analyze and visualize the database obtained. The results showed that the highest number of citations (citations) occurred in 2019 as many as 203 citations. In the publication trend, the most publications occurred in 2019 with 72 articles. Only one author collaborated with three other co-authors namely Kegler M.C. The most used term in the title is 'human' with 143 occurrences. The most used keyword term is 'cash transfer' with 11 passes. The most widely used term in the abstract is 'human' with 143 occurrences. Furthermore, the countries that published the most grant program articles were the United States with 246 articles, Canada with twenty-four articles, and Australia with eighteen articles.